Methicillin-resistant Staphylococcus aureus nasal carriage in neonates and children attending a pediatric outpatient clinics in Brazil - Vieira,Maria Aparecida (2014)
Background:In Latin America, few studies have been carried out on methicillin-resistant Staphylococcus aureus carriage in the pediatric population. We conducted a survey of nasal S. aureus carriage in neonates and in children attending the pediatric outpatient clinics in a large Brazilian city with high antimicrobial consumption.Methods:Pernasal swabs of neonates were collected upon admission and at discharge in four neonatal intensive care units and of children less than five years of age during outpatient visits. Methicillin-resistant S. aureus isolates were characterized for antibiotic susceptibility, mec gene presence, pulsed-field gel electrophoresis, spatype, SCCmec-type, multilocus sequence type, and presence of Panton-Valentine leukocidin genes.Results:S. aureus was carried by 9.1% and 20.1% of the 701 neonates and of 2034 children attending the outpatient clinics, respectively; methicillin-resistant S. aureus carriage was detected in 0.6% and 0.2%, of the these populations, respectively. Healthcare-associated methicillin-resistant S. aureus strains found in neonates from neonatal intensive care units and outpatients were genetically related to the Brazilian (SCCmec-III, ST239) and to the Pediatric (SCCmec-IV, ST5) clones. Community-associated methicillin-resistant S. aureus was only detected in outpatients. None of the methicillin-resistant S. aureus strains contained the Panton-Valentine leukocidin gene. Methicillin-resistant S. aureus strains related to the Brazilian clone showed multidrug resistance pattern.Conclusions:Despite the high antibiotic pressure in our area, and the cross transmission of the healthcare-associated methicillin-resistant S. aureus clones between neonatal intensive care units and outpatients, the prevalence of methicillin-resistant S. aureus carriage is still low in our setting.